INTERNALISASI KONSEP PLURALISME DI TENGAH KONFLIK SOSIAL (Perspektif Agama Hindu) - Komang Heriyanti (Sanjiwani: Jurnal Filsafat, 2022)
Recently, there has been a lot of news circulating about social conflicts that carry the name of religion. The news is very easy to reach every individual through social media. Not infrequently religious problems that were initially considered small became big problems. This is due to the presence of irresponsible elements. These elements tried to ignite the fire through social media, so that they could generate emotions for religious people who felt they were on the wrong side. If social problems are not handled wisely, it will only add to the commotion. Where the activity of attacking each other will become so. The problems that will be discussed in this paper are: (1) About social conflicts in society that carry the name of a religion and (2) Possible solutions to minimize these conflicts are studied from the perspective of Hinduism. The result of this paper is of course a qualitative study, this paper is based on the results of observations made in the field regarding social conflicts and how to minimize these problems. In Hinduism such things can be done through dharma discourse and dharmatula activities. Through dharma discourse activities, Hindus will get spiritual guidance from religious leaders so that they get an enlightenment in dealing with conflicts between religious communities. In dharmatula activities, Hindus also have the opportunity to have direct discussions related to religious issues in society.